2010
DOI: 10.1182/blood-2010-02-270777
|View full text |Cite
|
Sign up to set email alerts
|

Human multipotent mesenchymal stromal cells use galectin-1 to inhibit immune effector cells

Abstract: IntroductionMultipotent human mesenchymal stromal cells (MSCs) are plasticadherent cells with triangular and fibroblastoid morphologic features, which have the capacity to differentiate into osteoblasts, adipocytes, and chondrocytes. Furthermore, they express the cell-surface markers CD73, CD90, and CD105, while being negative for CD34, CD45, and human leukocyte antigen (HLA-DR). 1 Various tissues including bone marrow, fat, umbilical cord blood, or fetal tissues have been used as sources for MSCs. 2 Not only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
179
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(189 citation statements)
references
References 55 publications
4
179
0
6
Order By: Relevance
“…Some of these factors are constitutively produced by MSCs, such as HLA-G5, 49 prostaglandin E 2 (PGE 2 ), 50 and galectins. 51 The immunomodulatory effects exerted by MSCs can be augmented if the cells are activated by cytokines such as IFN-g. [52][53][54] It has also been shown that MSCs can be activated by stimulation of their Toll-like receptors. 55 Another important mediator of suppression by stromal cells is the T-cell inhibitory enzyme indoleamine-2,3-dioxygenase (IDO).…”
Section: Immune Modulation By Mscsmentioning
confidence: 99%
“…Some of these factors are constitutively produced by MSCs, such as HLA-G5, 49 prostaglandin E 2 (PGE 2 ), 50 and galectins. 51 The immunomodulatory effects exerted by MSCs can be augmented if the cells are activated by cytokines such as IFN-g. [52][53][54] It has also been shown that MSCs can be activated by stimulation of their Toll-like receptors. 55 Another important mediator of suppression by stromal cells is the T-cell inhibitory enzyme indoleamine-2,3-dioxygenase (IDO).…”
Section: Immune Modulation By Mscsmentioning
confidence: 99%
“…Data in Table 1 are in part summarized in (Chamberlain et al, 2008;Hall et al, 2006;Martino and Pluchino 2006;Pluchino et al, 2009b;Rojewski et al, 2008;Uccelli et al, 2008;Yuan et al, 2011). (Cusimano et al, 2012;Jaderstad et al, 2010) aracrine IDO-kynurenine MSCs (h) T cells, DCs T cell apoptosis, inhibition of antigen presentation (Lanz et al, 2010;Matysiak et al, 2008Matysiak et al, , 2011Meisel et al, 2004;Plumas et al, 2005 Bonnamain et al, 2012;Chabannes et al, 2007;Moll et al, 2011) Paracrine VEGF NPCs Microglia/macrophages Inhibition of microglial activation, proliferation and phagocytosis (Horie et al, 2011;Kim et al, 2009a;Mosher et al, 2012) Paracrine LIF NPCs Th17 cells Inhibition of Th17 cell differentiation (Cao et al, 2011;Horie et al, 2011;Kim et al, 2009a;Mosher et al, 2012) Paracrine Galectins MSCs/NPCs T cells Inhibition of T cell proliferation (Gieseke et al, 2010;Sioud 2011;Yamane et al, 2010Yamane et al, , 2011 Endocrine/Paracrine TSG-6 MSCs Macrophages Inhibition of macrophage activation, proliferation and phagocytosis (Fisher-Shoval et al, 2012;Lee et al, 2009;Roddy et al, 2011) EVs miR transfer MSCs/NPCs Multiple Post-transcriptional regulation (Bruno et al, 2009;Chen et al, 2010;…”
mentioning
confidence: 99%
“…Other factors believed to mediate the immunomodulatory effect of MSCs, such as galectin-1, are constitutively expressed at a high level. 17 We speculated that the factors involved and the underlying mechanisms differed based on the type of tissue, disease microenvironments and the species. In order to promote the clinical application of MSCs in CD, it is therefore necessary to identify the MSC-driven immunomodulators and related mechanisms that function in the CD microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…17,27 Therefore, we analyzed the possible role of MSCderived IGFBP7 in suppressing the tumor necrosis factor (TNF)-α and IFN-γ expression in T-cells. Expectedly, MSC con significantly inhibited the expression of proinflammatory cytokines by activated T-cells.…”
Section: Igfbp7 Knockdown In Mscs Restores the Proinflammatory Cytokimentioning
confidence: 99%
See 1 more Smart Citation